Effectiveness of Endorphin Massage and Positive Affirmations in Reducing Anxiety Levels Among Pre-Sectio Caesarea Patients - Rositawati, Rositawati; Putri, Siti Rafika; Efendi, Hernawati (Inspirasi Foundation, 2024)
Introduction: Facing a Caesarean section (C-section), patients often imagine the surgical process and various discomforts, leading to anxiety. Anxiety can result in both physical and psychological changes, such as an increased heart rate, elevated blood pressure, rapid breathing, fatigue, and an increase in fetal heart rate. Endorphin massage and positive affirmations offer benefits such as comfort and pain relief. This sense of relaxation and comfort is expected to reduce the anxiety experienced by patients before delivery. Objective: This study aimed to evaluate the effectiveness of endorphin massage and positive affirmations in reducing anxiety levels among pre-C-section patients. Method: This experimental study employed a pre-experimental design with a one-group pretest-posttest approach. The respondents included 30 pre-C-section patients at Sayang Hospital, Cianjur, selected through a total sampling technique. The research instrument used was the Hamilton Anxiety Rating Scale (HARS) questionnaire, which assessed the patients' anxiety levels before and after the intervention. Result: The study results, analyzed using the Paired Samples T-Test, showed a p-value of 0.000, which is <0.05. Conclusion: The findings indicate a significant reduction in anxiety levels among pre-C-section patients before and after receiving endorphin massage and positive affirmation interventions.